Compositional features and codon usage pattern of TP63 gene. (December 2019) - Chakraborty, Supriyo; Barbhuiya, Parvin A; Mazumder, Gulshana A; Deb, Bornali; Uddin, Arif
Graphical abstract: Highlights: Analysis of compositional features revealed variation in base content across TP63 gene isoforms were GC rich. The overall CUB of TP63 gene was low. Among 13 isoforms of TP63 gene, nature selected against the CTA codon in 8 isoforms. Nature favored five over-represented (RSCU>1.6) codons namely CTG, CAG, ATC, AAC and GCC during evolution. Abstract: The tumor protein p63encoded by the gene TP63 acts as a homologue of p53 protein. TP63 gene is the transformation factor with two initiation sites for transcriptional process and is related with stress, signal transduction and cell cycle control. The biasness in the preference of a few codons more frequently over other synonymous codons is the codon usage bias (CUB). Natural selection and mutational pressure are the two prime evolutionary forces acting on CUB. Here, the bioinformatic based analysis was performed to investigate the base distribution and CUB of TP63 transcript variants (isoforms) as no work was performed earlier. Analysis of compositional features revealed variation in base content across TP63 gene isoforms and the GC content was more than 50%, indicating GC richness of its isoforms. The mean effective number of codons (ENC), a measure of CUB, was 51.83, i.e. overall CUB of TP63 gene was low. Among 13 isoforms of TP63 gene, nature selected against the CTA codon in 8 isoforms and favored five over-represented (RSCU > 1.6) codons namely CTG, CAG, ATC, AAC and GCC during evolution. Correlation between overall nucleotide composition and its 3rd codon position revealed that both mutational pressure and natural selection moulded its CUB. Further, the correlation between ENC and aromaticity depicted that variation of CUB was related to the degree of aromaticity of p63 protein.